2008
DOI: 10.1103/physrevb.78.125208
|View full text |Cite
|
Sign up to set email alerts
|

First-principles study of Fe and FeAl defects in SiGe alloys

Abstract: First-principles, spin-polarized local-density-functional calculations are used to model interstitial iron ͑Fe i ͒ and its complexes with substitutional aluminum in dilute Si x Ge 1−x alloys ͑x Ͻ 8%͒. We considered both the effect of direct bonding between Fe i or Fe i Al with Ge atoms in the x → 0 limit and the evolution of the defect properties with the alloy composition. It is found that Fe i prefers Si-rich regions, but when placed near a Ge atom, its ͑0 / +͒ level is shifted toward the conduction band. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 67 publications
2
2
0
Order By: Relevance
“…Such an approach for modeling random Si 1Àx Ge x alloys has been previously justified. [26][27][28] The validity of the models was further confirmed, as the Si-Ge bond lengths and the topological rigidity parameter (without In atoms present) agreed well with those in the published literature. 29,30 III.…”
Section: Methodssupporting
confidence: 80%
“…Such an approach for modeling random Si 1Àx Ge x alloys has been previously justified. [26][27][28] The validity of the models was further confirmed, as the Si-Ge bond lengths and the topological rigidity parameter (without In atoms present) agreed well with those in the published literature. 29,30 III.…”
Section: Methodssupporting
confidence: 80%
“…3(b) shows that as the iron atom leaves away from the Ge atom, the relative energy goes down in the directions of both /1 01S and /1 01 S. Thus, it is expected that Fe will avoid Ge atoms. A. Carvalho et al reported the same result by a first principle calculation in Si x Ge 1 À x alloys [27]. The diffusion barrier of Fe away from Ge is lower than the diffusion barrier of Fe back to Ge, and the active energy of iron diffusion from a site to d site is even lower than the barrier of iron diffusion in CZ system, as shown in Fig.…”
Section: Sample [Ge] (Cm à 3 ) Association Dissociationsupporting
confidence: 62%
“…But the electrical activity of FeB complexes was stronger than that of Ge-Fe complexes [20] and FeB complexes could be a stronger recombination center that leaded to a bigger influence on the minority carrier lifetime than Ge-Fe complexes. Moreover, because Ge doping could increase the diffusion barrier of interstitial iron [14] and reduce the amount of FeB complexes in the Ge-doped mc-Si ingot, Ge doping could improve the minority carrier lifetime of the mc-Si wafers.…”
Section: Poly-simentioning
confidence: 93%